Pediline: Solução SaaS para Gerenciamento de Catálogo e Delivery - Brener, Filipe; Guilherme, Yan; Soares, Liziane Santos (Anais do Workshop de Sistemas de Informação (WSIS); 2024: Anais do XV Workshop de Sistemas de Informação, 2024)
Wearable technology and easy access to the internet have revolutionized various daily tasks, promoting convenience and comfort for users. This work aims to build and document delivery automation software compatible with different business sectors, specifically targeting small towns that do not yet have access to large brand applications. The proposed system is a multi-tenancy SaaS, developed in Java with the support of the Spring Framework. It will offer two user interfaces: one for managers, who will be able to manage products and sales, and another for end consumers, who will have access to an online catalog to make purchases. This paper also explores the impact of the pandemic on the growth of delivery services in small towns and the gap filled by Pediline.